KRONİK HEMODİYALİZ HASTALARINDA NONDİPPER HİPERTANSİYON NEDENLERİ - DURSUN, FADİME ERSOY (Fırat Üniveristesi, 2007)
Kronik hemodiyaliz (HD) hastalarında hipertansiyon (HT) yaygın bir problemdir. Bu çalışmanın amacı kronik HD hastalarında nondipper kan basıncının nedenlerini incelemek ve bu nedenlerin kardiyovasküler hastalık risk faktörlerini nasıl etkilendiğini araştırmaktır Çalışmaya antihipertansif ilaç kullanmayan normotansif 57 kronik HD hastası ile 19 sağlıklı kişi alındı. Tüm olgulara ambulatuar kan basıncı monitorizasyonu yapıldı. Ekokardiyografi ile sol ventrikül kitle indeksi (SVKİ), karotid arter intima-media kalınlığı (CCA IMT) ve damar kompliansı ölçümleri yapıldı. Bioimpedans analizi ile vücut sıvılarının ölçümleri yapıldı. Hastaların kan örnekleri HD seanslarının başlangıcında alındı. Hastalarda sistolik kan basıncı (SKB)'ndaki düşmeyle ilişkili parametrelerin Pearson korelasyon testi ile incelenmesi sonucunda yaş, SVKİ, ekstrasellüler sıvı/vücut ağırlığı (kg) ( ECF/kg), ECF/kg², high sensitif CRP (hsCRP), CCA İMT ile negatif ilişki gösterdiği saptandı ( sırasıyla r:-0.23, r:-0.39, r:-0.38, r:-0.39, p<0.05), Stepwise lineer regresyon analizi ile incelenen SKB'ındaki nondipping durumun nedenlerinin ECF/kg, hsCRP ve CCA İMT olduğu saptandı ( korelasyon katsayısı sırasıyla: -0.332, -0.243, - 0.251, p<0.05) Kronik HD hastalarının kardiyovasküler mortalitesini ve morbiditesini azaltmada sıkı volüm kontrolü sonucu hipertansiyonun kontrol edilmesinin yanı sıra, noktürnal kan basıncı yönünden dipper olmalarının da gerektiğini gözledik. Kronik HD hastalarında sıkı volüm kontrolü ile inflamasyon önlenebilir ve kardiyovasküler olaylardan korunulabilir. Fakat bu hipotezi kanıtlamak için daha fazla çalışma gerekmektedir.

Hypertension (HT) is a common problem in hemodialisis (HD). The aim of this study is to investigate the causes for nondipper HT in chronical HD patients and to explore their impact on risk factors for cardio-vascular diseases. 57 chronical HD patients with an average age of 50 ± 18 and 19 healthy individuals with an average age of 47 ± 13 were included in the study. Blood pressure parameters were measured by applying Ambulatory Blood Pressure Monitorization (ABPM) on the arm without fistula for the period between two HD sessions. Left Ventricle Mass Index (LVMI) Carotid Intima-Media Thickness (IMT), and vein compliance was measured by echocardiogramm. Bioimpedance analysis was applied before and immediately after the HD. Routine heamatological and biochemical analysis were performed in all cases, and high sensitive C - reactive protein (hsCRP), von Willebrand Factor (vWF), and homosisteine levels were measured. Statistically, the average Sistolic Blood Pressure (SBP) and Diastolic Blood Pressure (DBP) was found significantly higher in patients compared to the control group, however sistolic decrease rates were found lower (p<0.001). The average extracellular fluid/kg (ECL/kg) rate, LVMI, arteria carotis IMT, and hsCRP levels were significantly higher in the patient group (p<0.05). When classified according to nondipper and dipper patients, both groups showed similar average total SBP and DBP, ans similar average day SBP and DBP (p>0.05). average night SBP and DBP was found significantly higher in the nondipper group (p<0.05). ECL/kg and ECL/kg2 rates, LVMI, arteria carotis IMT, and hsCRP levels were significantly higher in the nondipper patient group, however the hemoglobin levels were lower (p<0.05). A negative relation was determined between the sistolic decrease rate and LVMI, ECL/kg, ECL/kg2, hsCRP and arteria carotis IMT (r:-0.23, r:-0.39, r:-0.41, r:-0.38, r:-0.32, r:-0.39, p<0.05, respectively). Using Stepwise linear regretion analysis it was shown that ECL/kg, hsCRP and arteria carotis IMT were the factors influencing the sistolic decrease. We showed that increase in ECL/kg, LVMI, and arteria carotis IMT, and hsCRP may be the causes for nondipper HT. We determined that a salt-poor diet and strict volume control is necessary to control HT in chronical HD patients. However, keeping patients normotensive with strict volume control does not necessarily mean a decrease in cardiovascular mortality and morbidity, but it is required that the patients are dipper in nocturnal blood pressure, too.
Causes for nondipper hypertension in chronical hemodialisis patients
Keywords: Nefroloji